Efek Pemberian Berbagai Dosis Pupuk Nitrogen Terhadap Pertumbuhan Dan Hasil Tanaman Kentang (Solanum Tuberosum L.) Varietas Medians - moch avif amirullah (AGRONISMA, 2021)
This study aims to determine the effect of various doses of nitrogen fertilizer on the growth and yield of Medians potato (Solanum tuberosum L.) varieties in the mediumlands and to obtain the optimum dose of nitrogen fertilizer which can increase the growth and yield of Medians potato varieties grown in the plains. medium. The research was conducted experimentally using a simple randomized block design (RAK) consisting of four doses of nitrogen fertilizer, namely D1 = dose 40 kg N / ha, D2 = dose 80 kg N / ha, D3 = dose 120 kg N / ha, D4 = dose 160 kg N / ha. The results showed that the dose of N fertilizer 120 kg ha-1 gave better growth and yield of potatoes compared to other treatments on parameters of plant height, stem diameter, number of leaves and leaf area. N treatment 120 kg ha-1 yielded chlorophyll 54.09 (su) with fresh tuber weight per plant 779.06 g tan-1 and tuber fresh weight per hectare 41.17 ton ha-1. The parameter of the number of stems of each treatment gave results that had no significant effect on each age of observation. Application of N fertilizer with a dose of 125.76 kg ha-1 and a dose of 114.042 kg ha- is the optimal dose to produce maximum leaf area and tuber weight per plant of 8434.91 cm2 and 735.05 g tan-1, respectively.